Geração automática de códigos de cenários de testes de aplicações de gerenciamento de processos de negócio a partir de modelos em BPMN - Moura, Jéssica Lasch de (2017)
Running automated tests is an important task for software quality. In the context of Business Process Management applications (BPM), however, the software testing is rarely addressed. In a survey on BPM application testing, no specific tools were found for the functional or nonfunctional testing of software developed with the help of Business Process Management Systems (BPMS). Given this, the option to perform tests using tools external to BPMS remains. To run tests using automation tools, you need to create some code. This creation can be laborious, especially considering applications that implement processes with many tasks or many possible flows. This work proposes an approach aiming to generate scenarios codes for automated testing of web applications, implemented with the support of a BPMS, from BPMN models, aiming to shorten the effort to build elements for testing. The work is mainly focused on functional tests and the automation tools selected for the test were: Cucumber, Lettuce and JDave; all used in conjunction with the Selenium tool. In order to achieve the objective of this work, the approach created: (i) generates a table of execution paths of the application from the analysis of flows in the BPMN model and (ii) generates the scenario code for the tests, using the flows obtained as input, to perform test using the tools mentioned above. To generate these elements, a tool has been created that traverses the BPMN file while evaluating the possible flows. For the test of the approach, the tool was applied to several processes of different repositories widely available. The approach was able to generate the desired elements for different types of processes, created through different BPMS and modeling tools.